Seismic design of reinforced concrete structures for controlled inelastic response design concepts (Thomas Telford, 1998)
This detailed guide will enable the reader to understand the relative importance of the numerous parameters involved in seismic design and the relationships between them, as well as the motivations behind the choices adopted by the codes.
Originally published in: CEB bulletin d'information, no. 236, 1997.
Keywords: Earthquake resistant design.; Reinforced concrete construction.; Buildings, Reinforced concrete -- Earthquake effects.; elektronické knihy; electronic books